Contribution to Study of Competition Between Cork Oak Crowns in the Ouled Bechih Forest (Algeria) - Touafchia Boutheyna; Rached-Kanouni Malika; Zerrouki Alia (Ekológia (Bratislava))
The discipline of silviculture is rapidly developing, based on stand structures or ecosystems, in which stands are managed according to species and structures. The objective of this study is to characterize the growth of cork oak dendrometric variables, and to determine and compare the different crown parameters and their effects on natural regeneration in the Ouled Bechih forest (Algeria). Eight plots of this forest were selected and they underwent a dendrometric study. The results obtained indicated that these plots were moderately dense. The analysis of dendrometric variables by variance analysis showed that there was a significant difference (p < 0.05). The distribution of individuals by height and diameter classes indicated a large representation of individuals with heights of 10–15 m and diameters of 27.5 < d ≤ 47.5 cm. The variables selected in the descriptive analysis have a low impact on the heterogeneity of this forest on height and diameter growth. The study of the different crown parameters showed that there was a difference between the plots, and indicated that cork oak trees have a large crown depending on their surface and diameter. These results show that the cork oak in the Ouled Bechih forest is characterized by trees of large diameter with medium heights, due to the predominance of older individuals with more developed crowns. This type of structure leads to strong inter-tree competition in the stand and a low rate of natural regeneration.